Using oxy-hydrogen gas to enhance efficacy and reduce emissions of diesel engine - Al-Dawody, Mohamed F. (2023)
The ever-increasing need for energy, along with diminishing petroleum supplies, has prompted the quest for renewable and sustainable alternative fuels. The goal of this research is to investigate theoretically the impact of using HHO gas on single-cylinder diesel engine characteristics using the simulation software diesel-RK model. Diesel fuel blended with 10% HHO gas is used and tested under different engine speeds. When 10% HHO gas was put into the engine, the thermal efficiency climbed to 31.5 percent and consequently, fuel consumption is reduced by up to 20 percent. The maximum reduction in BSN is 25% which is witnessed at 3500 rpm. The findings are corroborated by the findings of other studies. Among the most important outcomes that were obtained the peak combustion pressure was raised by 10% as compared to diesel fuel without HHO and the brake power enhances from (9% to 16%) when the engine speed is increased from (1500 to 3500) rpm.